Endoscopic ultrasound-guided ethanol ablation versus surgical resection of insulinomas - Jürgensen, Christian; Eckart, Marius; Haberbosch, Linus; Tacke, Frank; Sandforth, Arvid; Birkenfeld, Andreas L.; Overkamp, Dietrich; Daniels, Martin; Mogl, Martina; Goretzki, Peter; Strasburger, Christian; Mai, Knut; Spranger, Joachim; Jumpertz von Schwartzenberg, Reiner (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Purpose Insulinoma is a rare tumor of the pancreas that can lead to hypoglycemia. To date, the standard therapy is surgical resection. After the first case report of successful endoscopic ultrasound-guided (EUS) ethanol injection 16 years ago, the need for establishing an alternative treatment method remains unchanged given the high morbidity rates of surgery and its unsuitability in some patients.Materials and Methods Here, we provide retrospective data from 33 insulinoma patients that were treated at our center between 2010 and 2021. Of these, 9 patients were treated with EUS-guided ethanol injection and 24 underwent pancreatic surgery.Results The ethanol group was older (ethanol: mean ± SE 67.8±11.2 years vs. surgery: 52.3±15.7, p=0.014) with a higher Charlson Comorbidity Index (3.0 (1.0;4.0) vs. 1.0 (0.0;2.0), p=0.008). The lowest glucose values were similar between groups before (ethanol: 2.09±0.17 mmol/l vs. surgery: 1.81±0.08, p=0.158) and after (4.95±0.74 vs. 5.41±0.28, p=0.581) the respective treatments. Complications occurred more frequently in the surgery group (11 % vs. 54 %, p=0.026). One patient after prior partial pancreatectomy died postoperatively. The hospitalization time was significantly shorter in the ethanol group (4.78±0.78 days vs. 19.88±4.07, p<0.001).Conclusion EUS-guided ethanol injection can be similarly effective for the treatment of hyperinsulinemic hypoglycemia compared with pancreatic surgery but seems to be associated with less severe complications. This implies the need for prospective randomized trials in insulinoma patients with a low risk for malignancy.
Keywords: insulinoma; neuroendocrine tumor; interventional endoscopic ultrasound; pancreatic surgery; alcohol